Restoration of Lumbar Lordosis in Flat Back Deformity: Optimal Degree of Correction - Ki-Tack Kim; Sang-Hun Lee; Dae-Seok Huh; Hyo-Jong Kim; Jung-Youn Kim; Jung-Hee Lee (Asian Spine Journal, 2015)
Study DesignA retrospective comparative study.PurposeTo provide an ideal correction angle of lumbar lordosis (LL) in degenerative flat back deformity.Overview of LiteratureThe degree of correction in degenerative flat back in relation to pelvic incidence (PI) remains controversial.MethodsForty-nine patients with flat back deformity who underwent corrective surgery were enrolled. Posterior-anterior-posterior sequential operation was performed. Mean age and mean follow-up period was 65.6 years and 24.2 months, respectively. We divided the patients into two groups based on immediate postoperative radiographs-optimal correction (OC) group (PI-9°≤LL<PI+9°) and under-correction (UC) group (LL<PI-9°). We also classified the patients according to the PI of each patient-low PI group (PI<55°) and high PI group (PI≥55°). Radiological and clinical results were analyzed.ResultsPatients in OC group had significantly less correction loss and maintained normal sagittal alignment (sagittal vertical axis<5 cm), as compared to patients in UC group (p<0.05). LL of low PI group significantly maintained within 9° better than high PI group (p<0.05). Oswestry disability index (ODI) significantly decreased at last follow-up, as compared to preoperative state. However, there was no significant difference in last follow-up ODI between the groups.ConclusionsIn flat back deformity, correction of LL to within 9° of PI will result in better sagittal balance. Thus, we recommend sufficient LL to prevent correction loss, especially in patients with high PI.